PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7 E TERHADAP KEMAMPUAN REPRESETASI MATEMATIS SISWA - AZIZAH YUSRA AMALIYAH HARAHAP (JURNAL ILMIAH MAKSITEK, 2020)
This study aims to analyze whether there is an increase in the ability of mathematical representation of students using thelearning cycle 7 e learning model. The research method in this study uses quantitative quasi research experiments. Theresults of the study using quasi experiments are numbers so it is necessary to use descriptive statistical methods to describethe results of the study. The population that was the subject of the study was grade VII students of SMP 1 Negeri 1 Wardenof South Tapanuli Sipirok Sub-District in 2019/2020. With a class VII-4 sample as an experimental class and vii-1 controlclass. The instrument used in collecting data is an essay-shaped test. The hypothesis is tested with a t test, after a test ofnormality and homogeneity. The results showed there was an increase in mathematical representation of students using thelearning cycle 7 e learning model.